2023
DOI: 10.1002/adfm.202211900
|View full text |Cite
|
Sign up to set email alerts
|

Porous Organic Cage Induced Spontaneous Restructuring of Buried Interface Toward High‐Performance Perovskite Photovoltaic

Abstract: In perovskite solar cells (PSCs), the buried interface containing high concentrations of defects is critical for efficient charge extraction toward high-performance device. Herein, porous organic cage (POC) is introduced between tin dioxide and perovskite to spontaneously reconstitute the buried interface. Through the chemical linkage formed by polydentate chelation of POC with SnO 2 and perovskite, the buried interface achieves greatly reduced defect density and enhanced carrier extraction. More importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…21−25 For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/ perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. 24,26 Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk. 22 Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21−25 For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/ perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. 24,26 Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk. 22 Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSCs are suffering from significant non-radiative recombination losses originated from defect states of perovskites. Until now, numerous passivating strategies including solvent, composition, and interfacial engineering have been developed to enhance both efficiency and long-term stability. Specially, the buried interface between the perovskite layer and the underlying transport layer has been vastly investigated to minimize trap states and recombination losses as well as facilitate carrier extraction. For example, Dong et al and Gao et al have employed chlorobenzenesulfonic potassium salts and porous organic cages to passivate the buried tin oxide (SnO 2 )/perovskite interface, which results in better energy alignment, reduced trap states, and improved stability. , Similarly, Xu et al reported the successful use of daminozide as an interlayer to modify interface energetics and passivate defects at the interface as well as in perovskite bulk . Although high performance of PSCs has been achieved through the trap-state passivation, the mechanism is still complicated and excellent trap-state passivators are insufficient, which require further exploration and study.…”
Section: Introductionmentioning
confidence: 99%
“…The compact polycrystalline film formed by the FAPbI 3 component with better light absorption capacity and chemical stability stood out in 2015 . In the third period, which is still ongoing, the efforts have been mainly focused on passivation of defects at grain boundaries, upper surfaces, and buried interfaces of FAPbI 3 -based films, plus modulation of the transport materials. , …”
mentioning
confidence: 99%
“…3 However, a thorough investigation into the contribution of surface charge transfer to photovoltaic action and photovoltage is still lacking. 4,5 The lattice dynamics and electronic states of the free surface terminal and hetero-interface of perovskite have been the subject of extensive research in recent years. [6][7][8] Surface-localized electronic states can occur when the periodic structure of a perovskite terminates at its free surface.…”
mentioning
confidence: 99%
“…3 However, a thorough investigation into the contribution of surface charge transfer to photovoltaic action and photovoltage is still lacking. 4,5…”
mentioning
confidence: 99%